Measurement of the Buffalo Milk Fat Content using Creamatocrit Technique - D.D. Lorenzo; R.D. Dollete; M.P. Abella; P. Daniel; R. Vincent (Italian Journal of Animal Science, 2010)
The study was conducted to evaluate the use of Creamatocrit technique as an alternative in the measurement of the fat content of buffalo milk. The values of cream obtained from the buffalo milk through the Creamatocrit technique were compared and correlated with the fat contents obtained from the same animals using the Babcock technique. The mean cream content of the buffalo milk samples obtained through the Creamatocrit was 11.10 percent. This was significantly higher (P<0.05) by 30.54 percent (24 to 38 percent) than the fat content obtained from the Babcock technique, which was 7.71 percent. The fat content is positively correlated (0.89) with the cream content of milk. More precise readings were observed in the use of the Creamatocrit technique as compared to the use of Babcock technique. Regression analysis gave off to equation defined as: Y = (-0.01 + 0.6) (X).